Spontaneous external biliary fistula uncomplicated by gallstones. - Birch, B. R. (BMJ Group, 1991)
External biliary fistulae are rare. Only 65 cases have been reported in the literature and in each instance gallstones were a complicating factor. We report in this paper the first case of spontaneous external (cholecystocutaneous) biliary fistula uncomplicated by gallstones.